Graph analysis of cross-shareholdings among organisations - Sim, Shan Qin (Nanyang Technological University, 2020)
The study is to investigate the reasons and the impact of cross-shareholdings in the Singapore Stock Exchange (SGX). After investigation, a small number of cross-shareholdings was found between listed companies, these resulted in a very sparse graph. It was evaluated that the reasons for these cross-shareholdings are portfolio diversification, consolidation of the company’s position in their sectors or/and to prevent hostile takeovers. Graph decomposition was done on the sparse graph to obtain each cluster of companies and it was found that most cross-shareholdings was either done by a family conglomerate or state-owned entities using a certain graph structure. This is to ensure absolute voting rights and/or to enjoy the dividends payout. PageRank and Out-degree centrality were used to identify important clusters and companies.